Economic Burden of Type 2 Diabetes Mellitus among the Patients Attending Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Diabetes Mellitus (DM) is a major concern for the developed as well as developing countries. It poses with enormous disabilities and economic burden to the victims. The treatment cost of diabetes is increasing day by day. Aim: To ascertain how type 2 diabetes mellitus is incurring economic burden to the patients. Materials and Methods: This descriptive cross sectional study was conducted during the period from January to June 2010 on 110 type 2 diabetes mellitus patients attending Combined Military Hospital, Dhaka. The patients were selected conveniently and data were collected by face to face interview with the help of a semi-structured questionnaire. For estimation of economic burden, both direct and indirect treatment costs were calculated. Results: The study revealed that majority (36.4%) of the patients were in the age group of 46-55 years with the mean age of 53.65 (+10.44) years. Majority (60.0%) of them had lower monthly family income (Tk.5, 000-Tk.10, 000) and 36.4% of them lived in urban area. Most of the patients (90.9%) were under treatment with drug, diet control and physical exercise. Regarding sources of fund for treatment, 31.8% patients used their savings while 27.3% took loan, 20% got help from relatives and the remaining 20.9% got donation and sold wealth. Average treatment cost incurred by the patients was estimated to Tk. 5543.35 (+1273.29). Average direct treatment cost was estimated to Tk.2656.88 (+1367.23) of which average drug cost was Tk.653.36 (+476.36), investigation cost was Tk.596.73 (+375.56), travel cost Tk.530.31 (+795.46), attendant cost Tk.865.87 (+734.22) and consultation fee was Tk.244.48 (+167.22). Average indirect cost was calculated to Tk.3081.27 (+1275.91) which was only due to loss of income due to illness. Conclusion: The study findings will enable the health policy makers and health care providers at different levels to provide need based cost-effective health care services to reduce the economic burden of diabetes mellitus patients. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18718 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 8-13